Penerapan Model Problem-Based Learning dengan Media Mofil untuk Meningkatkan Hasil Belajar Peserta Didik - Delismar, Delismar (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to apply the Problem-Based Learning (PjBL) with mofil media in science. This research was also endeavored to improve the students’ learning curiosity, involvement, activity, cooperation, discipline and learning outcomes of the ninth graders in the State Junior Secondary School 5 in Jambi. An Classroom Action Research was designed with two cycles and two sessions each cycle. Each action was observed using an instrument for both the students and teachers. While the students’ achievement was measured using a written test.   The research results show that the students’ achievement in science is improved in cycle 2. While the students’ learning curiosity, involvement, activity, cooperation, and learning discipline are improved in cycle 2 after the implementation of the Problem-based Learning with mofil media.